DIFFERENTIATION OF ANTEMORTEM & POSTMORTEM BURNS BY HISTOPATHOLOGICAL EXAMINATION (Journal of Forensic Medicine & Toxicology, 2015)
Burns constitute a major cause of death and morbidity whatever reason may be, in the world and in this country too. Undoubtedly a severe burn is the most devastating injury a person can sustain and yet hope to survive. In the medico-legal setting, determination of whether the burns seen on a body are ante mortem or post-mortem in nature is of paramount importance. Whether the person was alive at the times of sustaining burns needs meticulous scrutiny as the person might have had died due to fatal burn injury or died due to some disease or sudden assault or injury and suffered burns later on. The differentiation between antemortem and postmortem burn is dependent upon the presence of vital reaction, as to be seen by histological examination. In the present study effort were made to differentiate antemortem and postmortem burns by histopathology of burnt and junctional skin. Blisters were present in 36% cases, pus was present in 54% cases, signs of healing were present in 26% cases and red line of demarcation was present in 88% cases. Histopathological findings of burnt and junctional skin showed separation of epidermis from dermis and breaking of epithelium in 90% cases respectively, vacuolisation and petechial  haemorrages in 76% cases respectively; epithelial cells were flattened and elongated in 86% cases respectively. Capillary dilatation was present in 84% cases, odema and margination of leucocytes were present in 74% cases respectively, congestion and infiltration were present in 90% cases respectively. Skin was not available in 10% cases as the bodies were charred. Antemortem burns were present in 96% cases and postmortem burns in 4% cases. So histopathological examination plays a eminent role importance in differentiation of antemortem and postmortem burns.
Keywords: Burns; Histopathological examination; Junctional skin